Influence of Annual Ornamental Flowers (Asteraceae) on the Relative Abundance of Honey Bee Species in the Hot Semi-arid Environment - Gupta, Dipak Kumar; Shukla, A K; A, Keerthika; Noor Mohamed, M B; Jangid, B L (Annals of Arid Zone, 2020)
Honey bees are an important component of the agricultural ecosystem and provide valuable pollination service. Cultivation of annual ornamental flowering plants is being recognized as a suitable options to compensate for the loss of natural floral resources for conserving the declining population of the honey bee. The capitulum/ inflorescence of commonly grown annual ornamental flowers of the Asteraceae family differs in morphology. The morphology of flowers affects the abundance and diversity of bee species. Therefore, the present study was conducted with an aim to study the influence of commercially cultivated flowering plants of India (Calendula officinalis, Chrysanthemum indicum, Glebionis segetum, Tagetes patula and Tagetes erecta) on honey bee diversity and abundance in the hot semi-arid environment. The capitulum of these plant species differed significantly in length and diameter of the corolla tube. It was observed that dwarf (Apis florea) and giant (Apis dorsata) honey bee were the most common visitors, however, the abundance of both bee species was significantly different (P<0.01) on different plant species. Plants with relatively longer (15.25-18.9 mm) and wider corolla tube (Tagetes erecta and Tagetes patula) were visited by both the bee species. However, plants having short (5.0-6.5 mm) and narrow (1.0-1.33 mm) corolla tubes (Calendula officinalis, Chrysanthemum indicum, Glebionis segetum) were dominantly visited by only Apis florea. Therefore, the cultivation of Tagetes patula and Tagetes erecta may enhance the population and conservation of both Apis florea and Apis dorsata, while Calendula officinalis, Chrysanthemum indicum, and Glebionis segetum may only enhance the population of Apis florea in the arid and semi-arid zone of India. Key words: Flower size, Apis dorsata, Apis florea, arid region, foraging behavior